2021
DOI: 10.1186/s13643-021-01702-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal progesterone for prevention of preterm birth in asymptomatic high-risk women with a normal cervical length: a systematic review and meta-analysis protocol

Abstract: Background Preterm birth (PTB) is estimated to affect 14.9 million babies globally every year. Global rates of PTB continue to increase from 9.8 to 10.6% over a 15-year period from 2000 to 2014. Vaginal progesterone is commonly used by clinicians as a prevention strategy, with recent evidence affirming the benefit of vaginal (micronised) progesterone to prevent PTB in women with a shortened cervix (< 25 mm). Given the low incidence of a short cervix at mid-gestation in high-risk populations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Em mulheres com gestação única e colo curto ao US, a via vaginal apresentou maior redução de partos <34 semanas quando comparado a outras vias 1,19,21,51,60 . Care et al 9 , em revisão sistemática e metanálise, observaram que a progesterona vaginal deve ser considerada como a melhor escolha para gestações únicas assintomáticas com risco de parto pré-termo devido a colo curto ou história de parto pré-termo espontâneo anterior 9 .…”
Section: Progesteronaunclassified
“…Em mulheres com gestação única e colo curto ao US, a via vaginal apresentou maior redução de partos <34 semanas quando comparado a outras vias 1,19,21,51,60 . Care et al 9 , em revisão sistemática e metanálise, observaram que a progesterona vaginal deve ser considerada como a melhor escolha para gestações únicas assintomáticas com risco de parto pré-termo devido a colo curto ou história de parto pré-termo espontâneo anterior 9 .…”
Section: Progesteronaunclassified
“…The EPPPIC trial concluded that progesterone also works when the cervical length is between 25 and 30 mm, but the number of included women was small (57). There is also some unclarity whether women with a previous preterm birth and normal cervical length should be offered progesterone (57,128,129). The same applies to whether progesterone works for other risk factors of preterm birth, e.g., cervical conization (130) or for newly identified risk factors as a history of a second stage caesarean delivery (131,132).…”
Section: Research Implicationsmentioning
confidence: 99%